Knowledge status of x-ray department managers of Istanbul private hospitals about hospital accreditation - (:unkn) unknown (My University, 2018)
JCI accreditation standards are an undertaking that provides continuity of improvement and development work that is guided by the development of patient care quality at the most appropriate level, the provision of a reliable patient care environment, and the reduction of the risks of patient and service providers. The purpose of our work is to determine the extent to which x-ray department managers from the Istanbul city's private hospitals who are preparing for accreditation or have successfully completed the accreditation can apply the JCI accreditation standards, their knowledge level and their attitude about it. The study's universe constitutes a total of 111 people serving as managers in the radiology departments of private hospitals operating in the province of Istanbul. A survey form was applied in the study. As a result, the education of the managers of the radiology services should be under the management of the persons with the expertise and experience.